A case report: stent implantation to treat coarctation of persistent 5th aortic arch associated with interrupted 4th aortic arch. Issue 2 (23rd May 2019) - Kato, Atsuko; Ohashi, Naoki; Nishikawa, Hiroshi
Abstract: Background: Persistent 5th aortic arch is a rare cardiac anomaly that is usually surgically corrected during infancy or early childhood if it is associated with coarctation of the aorta. Here, we report an adult with coarctation of the 5th aortic arch who was successfully treated by stent implantation. Case summary: An asymptomatic 32-year-old woman presented with hypertension and a significant arm–leg difference in pressure. On suspicion of coarctation of the aorta, a chest computed tomography was performed, leading to a diagnosis of an interrupted 4th aortic arch with coarctation of a persistent 5th aortic arch. Percutaneous catheter intervention using a PALMAZ large stent dilated to 12 mm resulted in a minimal peak-to-peak pressure gradient. The patient was discharged home after a 2-day monitoring without hypertension and arm–leg blood pressure difference. She remained normotensive with a patent aortic arch on echocardiography performed 10 months after treatment. Discussion: As for simple coarctation of the aorta, stent implantation was feasible and effective in an adult patient with coarctation of the 5th aortic arch.